Lecturers’ Feedback in Speaking Class (A descriptive Study at Ar-Raniry State Islamic University) - Fakhrul Azmi; Sofyan A. Gani; Bukhari Daud (Universitas Syiah Kuala, 2019)
This qualitative study attempted to investigate the types of feedback used by the lecturers and the most frequent type used in speaking class at English Department of Ar-Raniry State Islamic University (UIN Ar-Raniry). The participants of this study were two lecturers who were teaching intermediate speaking at English department of UIN Ar-Raniry. Therefore, two classroom observations were recorded and transcribed. The observations were conducted four times of each class. The data analysis was done by using Miles and Huberman’s (1984) model including data reduction, data display, and conclusion. The findings of this study revealed some significant results. There were five types of corrective feedback used by the lecturers in teaching speaking at English department of UIN Ar-Raniry. It includes recast, elicitation, clarification request, repetition, and translation. Further, the type of feedback most frequently used by the lecturers in teaching speaking was recast followed by translation, clarification request, elicitation and repetition.